Peran Dimensi Parenting terhadap School Engagement melalui Basic Need Satisfaction pada Siswa SMP “X” Bandung - Amanda Putri; Yuspendi Yuspendi; Jane Savitri (Universitas Kristen Maranatha, 2024)
The purpose of this research is to find the model and path description of how parent involvement, parent autonomy support and parental structure fulfill the need for autonomy, need for competence, and need for relatedness which contributes to school engagement found on students at “X” Junior Highschool, Bandung. According to path analysis done in this research, it is concluded that: parent involvement is significantly influential towards the need for autonomy, need for competence and need for relatedness; parental structure is only significantly influential towards the need for competence and the need for relatedness; the need for autonomy only significantly influential towards the emotional engagement and cognitive engagement; the need for competence is only significantly influential towards the behavioral engagement and emotional engagement; while the need for relatedness is only significantly influential towards the emotional engagement and cognitive engagement.